Dapatkah CSR Disclosure dan Corporate Governance Menangkap Manajeman Laba, dan Manajeman Pajak? - Vita Aprilina (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2019)
The purpose of this study was to determine whether Corporate Social Responsibility Disclosure and Corporate Governance capture the phenomenon of Tax Management with Earning Management as an intervening variable. The research method used in this study is quantitative research methods. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in the period 2013 to 2015. Sampling using purposive sampling technique with certain criteria. The sample in this study were 84 manufacturing companies listed on the Indonesia Stock Exchange. The data used is secondary data form financial reports and annual reports obtained from the Indonesia Stock Exchange website.Data analysis techniques using multiple linear regression and path analysis. The results showed that CSR disclosure and Corporate Governance had no effect on Tax Management and earning Management, while earnings management had a significant positive influence on tax management in manufacturing companies in Indonesia.